Éditorial/Editorial [Summer 2009] - Déom, Esther (Relations Industrielles / Industrial Relations, 2009)
Introduction : Doctorat honorifique décerné au professeur Mark Thompson/Honorary Doctorate Awarded to Professor Mark Thompson
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions